Natural inflation from 5D SUGRA and low reheat temperature - Filipe Paccetti Correia; Michael G. Schmidt; Zurab Tavartkiladze (Nuclear Physics B, 2015)
Motivated by recent cosmological observations of a possibly unsuppressed primordial tensor component r of inflationary perturbations, we reanalyze in detail the 5D conformal SUGRA originated natural inflation model of Ref. [1]. The model is a supersymmetric variant of 5D extranatural inflation, also based on a shift symmetry, and leads to the potential of natural inflation. Coupling the bulk fields generating the inflaton potential via a gauge coupling to the inflaton with brane SM states we necessarily obtain a very slow gauge inflaton decay rate and a very low reheating temperature Tr≲O(100) GeV. Analysis of the required number of e-foldings (from the CMB observations) leads to values of ns in the lower range of present Planck 2015 results. Some related theoretical issues of the construction, along with phenomenological and cosmological implications, are also discussed.